Effect of catheter selection in hypospadias repair (Annals of Medical Research, 2021)
Aim: The effects of catheter use on postoperative complications in patients undergoing hypospadias repair remains controversial. The aim of this study was to evaluate the effectivity of silicone and feeding catheters on surgical outcomes in patients undergoing hypospadias repair.Material and Methods: The retrospective study included 169 patients with distal and midpenile hypospadias who were operatively treated with tubularized incised plate urethroplasty between July 2014 and July 2018. A feeding catheter was used in 79 patients (Group A) and a silicone catheter was in 90 patients (Group B). Postoperative complications including catheter-related complications (catheter occlusion, urine leak around the catheter, and spontaneous withdrawal) and hypospadias-related complications (urethrocutaneous fistula, meatal stenosis, urethral stenosis, and glans dehiscence) were recorded for each patient.Results: The age of the patients ranged between 6 months and 15 years. The incidence of catheter-related complications was significantly higher in Group A compared to Group B (p0.021). The overall incidence of hypospadias-related complications was 5.1% in Group A as opposed to 3.3% in Group B and no significant difference was found between the two groups with regard to postoperative complications.Conclusion: Although catheter selection had no effect on hypospadias-related complications, the use of feeding catheters led to a higher incidence of catheter-related complications, which is likely to increase the anxiety levels of the parents.